2021
DOI: 10.1017/erm.2021.18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of the HPV16 early genes and LCR. Present and future perspectives

Abstract: Human papillomavirus 16 (HPV16) infection is the aetiologic factor for the development of cervical dysplasia and is regarded as highly carcinogen, because it is implicated in more than 50% of cervical cancer cases, worldwide. The tumourigenic potential of HPV16 has triggered the extensive sequence analysis of viral genome in order to identify nucleotide variations and amino acid substitutions that influence viral oncogenicity and subsequently the initiation and progression of cervical cancer. Nowadays, specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 154 publications
0
13
0
Order By: Relevance
“…No positive selection sites for HPV52 E6 and E7 genes have been reported in central and Southwest China [ 38 , 39 ]. In addition, selective pressure analysis from non-Asian population showed different results, with 10R, 14H, 83V in HPV E6 and 85G in HPV16 E7 under positive selective pressure [ 40 , 41 ]. Therefore, these results indicate that genetic variations among HPV types may lead to biological advantages through fixed mutations in their genomes and that even small variations might lead to minor adaptive improvements.…”
Section: Discussionmentioning
confidence: 99%
“…No positive selection sites for HPV52 E6 and E7 genes have been reported in central and Southwest China [ 38 , 39 ]. In addition, selective pressure analysis from non-Asian population showed different results, with 10R, 14H, 83V in HPV E6 and 85G in HPV16 E7 under positive selective pressure [ 40 , 41 ]. Therefore, these results indicate that genetic variations among HPV types may lead to biological advantages through fixed mutations in their genomes and that even small variations might lead to minor adaptive improvements.…”
Section: Discussionmentioning
confidence: 99%
“…The LCR contains the early promoter and various transcriptional regulatory sites of involved in viral DNA replication and transcription [ 32 , 33 ], such as E2, YY1, NF1, FOS, NFKB1, and others. Several studies have suggested that certain LCR variants of HPV16 may play an important role in viral persistence and the development of cervical cancer [ [34] , [35] , [36] ]. For example, Dong et al suggested that the mutation of the LCR sequence of HPV16-positive cervical cancer patients is mainly located in the YY1 binding region [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular transcription factors including Ying-yang 1(YY1), Nuclear-factor 1(NF1), Activator protein 1 (AP1), Glucocorticoid receptor (GR) and Progesterone receptor (PR), among others, can bind to the cognate site in this region for viral gene expression regulation. Additionally, viral E2 protein binding to cognate sites inside the LCR stimulate or to suppress the viral transcriptional activity with effects depending on different HPV types and variants [ 19 , 20 , 21 ]. The E region encodes all the non-structural E1, E2, E4, E5, E6 and E7 proteins, with them having major functions in viral replication and cell transformation [ 22 ].…”
Section: Human Papillomavirus: Classification Structure and Replicati...mentioning
confidence: 99%